Traceability technologies tailored to scaling biofortified crops in Nigeria - CGIAR Research Program on Agriculture for Nutrition and Health (2020)
Project on implementing this technology for improving traceability of biofortified maize reached the finals in the CGIAR Data Innovation Challenge, recognizing it as a promising proof of concept, but has not yet been piloted.